2022
DOI: 10.3390/antibiotics11081083
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Interaction of Gentamicin with Ceftriaxone and Azithromycin against Neisseria gonorrhoeae Using Agar Dilution Method

Abstract: The susceptibility to gentamicin of N. gonorrhoeae isolates collected in three Chinese provinces and the correlation among the MICs of gentamicin, azithromycin, and ceftriaxone were investigated in this study. The effects of combinations from those three antibiotics were also in the scope of this study to determine the efficacy of gentamicin as a combination therapeutic drug. The agar dilution method was used to measure the minimum inhibitory concentrations (MICs) of ceftriaxone, azithromycin and gentamicin on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The ∑ FICI values were interpreted as follows: total synergistic ∑FIC ≤ 0.5, partial synergism (0.5 < ∑FIC < 1), additive, ∑FIC = 1, indifference 1 < ∑FIC < 4 and antagonistic (∑FIC ≥ 4) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ∑ FICI values were interpreted as follows: total synergistic ∑FIC ≤ 0.5, partial synergism (0.5 < ∑FIC < 1), additive, ∑FIC = 1, indifference 1 < ∑FIC < 4 and antagonistic (∑FIC ≥ 4) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The non-parametric Mann–Whitney U -test was implemented to examine the differences between MICs of eight antibiotics in different growth supplement. 14 …”
Section: Methodsmentioning
confidence: 99%
“…In the standard operation of the agar dilution method, 1% Vitox was recommended as a growth supplement, while sterile defibrinated sheep blood and bovine hemoglobin were used as substitutes for Vitox in some hospitals and research institutions. 14 , 15 For those institutions, the possible reasons for choosing sheep blood or hemoglobin as growth supplements were that these are more accessible and less costly. Hemoglobin was also used as a nutrient supplement in the Thayer Martin Agar used to isolate and culture N. gonorrhoeae .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that gentamicin can successfully treat gonorrhea, especially when combined with other antibiotics such as azithromycin or ceftriaxone. The development of medication resistance may be slowed down with the use of this combination therapy (Xu et al, 2022). (Figure 4)…”
Section: Gentamicinmentioning
confidence: 99%